The effect of spraying some macro and micro elements on the seed quality and quantity of maize hybrid single cross 704 - Ali Jalilian; Samira Asgari; Saeid Jalali Honarmand; Mahmoud Khoramivafa; Aziz Moradi (علوم و فناوری بذر ایران, 2020)
This experiment was conducted at Mehrgan Agricultural Research Station, Kermansha, Iran, in 2012. The maize parents of hybrid 704 cultivar was cultivated in a randomized complete block design with three replications. The treatments includes: 1-ammonium nitrate (1/3 before planting and 2/3 after planting) 2-solupotas 3-iron chelate, 4-zinc sulfate, 5-manganes sulfate 6- boric acid, 7- Combine treatments 1 to 6 with each other. 8- Combine treatments 1 and 2 with each other. 9- Combine treatments 3 to 6 with each other. 10- Control (without spraying). The applied treatments were sprayed in three stages: 1- growth stage from 6 to 8 leaves 2- maximum leaf area index 3- after pollination. The length of plots was 7 meters and width was 4.5 meters (including 4 mother line and 2 father line) with spacing rows of 75 cm and plant spacing on the 18 cm row. The cultivation was carried out on May 1 and irrigation system was sprinkler. The treats measured was include macro and micro elements in seed, germination percentage, seedling vigor index (SVI), germination rate and Seedling growth rate (SGR) for each treatment. The results showed that foliar application did not significantly differ in the amount of nutrients in corn seed. Despite the lack of significant difference in the amount of nutrients in the seed, seedling growth and germination rate were superior in some treatments, so that the highest seedling growth was observed in potassium spraying treatment. The highest rate of germination was also due to spraying with high consumption elements.